Lead-acid battery wastewater treatment method
The treatment of lead-acid battery wastewater by modifying chitosan-based magnetic biochar adsorbent and chemical flocculation method has solved the problems of complex operation and high energy consumption in the prior art, and achieved the effect of efficient removal of lead ions and suspended matter.
Patent Information
- Application Number
- CN202510009113.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
The existing lead-acid battery wastewater treatment technology is complex in operation and has high energy consumption, making it difficult to effectively remove lead ions and suspended matter in the wastewater.
The modified chitosan-based magnetic biochar adsorbent is used for primary and secondary adsorption treatment, combined with lime emulsion, polymer aluminum chloride and polyacrylamide for reaction and flocculation treatment, and finally the wastewater purification is achieved through sedimentation and dehydration treatment.
It improves the adsorption efficiency of lead ions in wastewater, simplifies the treatment process, reduces energy consumption, and realizes effective purification of wastewater.
Smart Images

Figure BDA0005227831700000151 
Figure BDA0005227831700000161
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a lead-acid battery wastewater treatment method. Background Art
[0002] Lead-acid batteries produce lead-acid wastewater during the production process. The composition of lead-acid wastewater is complex, with high toxicity, strong acidity, and difficulty in degradation. If it is not treated, it will seriously affect the health of the operators and cause serious harm to the surrounding environment. In the process of manufacturing lead-acid batteries, the discharged wastewater mainly comes from acid preparation, plate coating, formation and other processes or ventilation and dust removal water, rinsing wastewater of formation plates, cleaning wastewater after lead-acid batteries are assembled, workshop lead smoke wastewater, lead dust wastewater treatment, and wastewater generated in workshop floor washing, centralized bathing wastewater, laundry lead wastewater, and high-salt wastewater generated by pure water preparation. These wastewaters mainly contain lead powder, molten lead, lead sulfate, sulfuric acid and some other organic additives and engine oil. Lead is a type of pollutant, which is very harmful if not properly handled.
[0003] At present, the methods for treating lead-containing wastewater include chemical precipitation, ion exchange and electrodialysis. Chemical precipitation is the most widely used technology for treating lead-containing wastewater. The existing treatment process is complex and energy-intensive. Summary of the invention
[0004] In view of this, the present invention provides a lead-acid battery wastewater treatment method to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention to solve its technical problem is:
[0006] A method for treating lead-acid battery wastewater comprises the following steps:
[0007] (1) Collecting wastewater: Collecting lead-acid battery wastewater and storing it in a wastewater storage tank, and comprehensively adjusting the water quality and water volume of the lead-acid battery wastewater to ensure uniform quality and volume;
[0008] (2) Primary adsorption treatment: The wastewater in the wastewater storage tank in step (1) is transported to the primary adsorption tank, the pH value is adjusted to 5-6, an adsorbent is added at a dosage of 0.5-1.5 g / L for adsorption treatment for 6-10 hours, and filtered to obtain a filtrate of the primary adsorption treatment;
[0009] (3) Reaction treatment: adding the filtrate from the primary adsorption treatment in step (2) into a reaction tank, adding lime emulsion to adjust the pH value to 7.5-8.5, then adding polyaluminium chloride to react, and after the reaction is completed, adding polyacrylamide to flocculate to obtain a mud-water mixture;
[0010] (4) Sedimentation treatment: The mud-water mixture in step (3) is transported to a sedimentation tank to produce physicochemical sludge by sedimentation reaction, and the upper clear liquid and lower sludge are collected;
[0011] (5) Dehydration treatment: The lower layer of sludge in step (4) is transported to a sludge thickening tank for reduction adjustment, and then pumped into a high-pressure diaphragm plate and frame filter press for further dehydration and reduction to obtain a filter press filtrate and dehydrated sludge;
[0012] (6) Secondary adsorption treatment: the supernatant in step (3) and the filter press filtrate in step (5) are mixed and transported to a secondary adsorption tank, the pH value is adjusted to 6 to 9, an adsorbent is added at a dosage of 0.5 to 1.5 g / L for 6 to 10 hours, and filtered to obtain a filtrate treated with secondary adsorption;
[0013] (7) Testing and collection: Testing the filtrate from the secondary adsorption treatment in step (6). If the filtrate meets the standard, it is collected and put into the clean water tank. If it does not meet the standard, it is returned to the primary adsorption tank or the secondary adsorption tank according to the standard for further treatment until it meets the standard.
[0014] Wherein, the adsorbents in step (2) and step (6) are both modified chitosan-based magnetic biochar adsorbents.
[0015] Furthermore, the dosage of lime emulsion in step (3) is 2-3 kg / m 3 .
[0016] Furthermore, in the step (3), the Al2O3 content in the polyaluminium chloride is 20% to 30%, and the dosage of the polyaluminium chloride is 0.1 to 0.45 kg / m 3 .
[0017] Furthermore, in step (3), the molecular weight of polyacrylamide is 10 million to 14 million, and the dosage of polyacrylamide is 0.005 to 0.01 kg / m 3 .
[0018] Furthermore, the sedimentation tank in step (4) is a vertical flow type, and the surface load of the sedimentation tank is 0.1 to 1.0 m 3 / (m2·h).
[0019] Furthermore, the preparation method of the modified chitosan-based magnetic biochar adsorbent comprises the following steps:
[0020] S1. Mix the biomass with Fe(NO3)3·9H2O and add them to anhydrous ethanol, stir them evenly at room temperature and disperse them by ultrasonication, dry them at 60-70°C, put the dried biomass in a container, put it in a tubular furnace and introduce nitrogen, heat it to 500-600°C in a nitrogen atmosphere, sinter it at a constant temperature, and cool it at room temperature to obtain magnetic biochar;
[0021] S2, stirring the polypropylene glycol and heating it to 30-40°C, slowly adding itaconic anhydride and 4-dimethylaminopyridine in sequence, then heating it to 50-60°C and stirring for 1-2h, and cooling it at room temperature to obtain a modifier;
[0022] S3, weigh 10-20 parts of chitosan powder, 100-120 parts of 1% acetic acid solution, 6-10 parts of magnetic biochar, 12-16 parts of modifier, 6-8 parts of polyvinyl alcohol, and 40-50 parts of 1% sodium tripolyphosphate solution respectively by weight;
[0023] S4. Add chitosan powder to acetic acid solution, stir to dissolve at room temperature, then add magnetic biochar and modifier, stir evenly and heat to 60-70°C in a water bath, then add polyvinyl alcohol and continue stirring until mixed evenly, then slowly add dropwise to sodium tripolyphosphate solution, let stand for aging after the addition is complete, filter, take the solid and dry to obtain a modified chitosan-based magnetic biochar adsorbent.
[0024] Furthermore, the biomass in step S1 is at least one of peanut shells, buckwheat shells, coconut skins, wood chips, and bamboo chips.
[0025] Furthermore, the mass ratio of the biomass to Fe(NO3)3·9H2O in step S1 is 1:0.5-2.
[0026] Furthermore, the heating rate in step S1 is 5-10° C. / min, and the sintering time is 2-3 h.
[0027] Furthermore, the mass ratio of polypropylene glycol, itaconic anhydride and 4-dimethylaminopyrrolidone in step S2 is 40:22:0.1-1.
[0028] The beneficial effects of the present invention are:
[0029] The present invention discloses a method for treating lead-acid battery wastewater.
[0030] (1) The present invention uses chitosan as a carrier, modifies it and loads magnetic biochar as an adsorbent. Since there are a large number of hydroxyl groups and amino groups in the chitosan molecule as active sites, it can bind to Pb through chelation, hydrogen bonding or electrostatic attraction. 2+ The chitosan structure was modified by using polypropylene glycol and itaconic anhydride, and more active sites were introduced on the chitosan to improve its adsorption capacity. The pores of the adsorbent were increased while protecting the hydroxyl and amino groups on the surface of the chitosan, making the surface of the adsorbent rough and not smooth, increasing the surface area of the adsorbent, which was beneficial to the adsorption of Pb 2+ Contact with the adsorbent makes more active sites on the adsorbent surface available, thereby improving the adsorption capacity. 2+The lone pair of electrons on the O atom of the ether bond is used to form a bond, which reduces the electron density of the adjacent C atom and forms a CO-Pb bond, thereby further improving the adsorbent's affinity for Pb. 2+ Adsorption effect;
[0031] Biochar can bind Pb through π-π interaction and hydrogen bonding. 2+ Adsorbed to oxygen-containing functional groups such as C=O, CO and OH in the material, the surface molecules of biochar can react with Pb 2+ Producing van der Waals force, Pb 2+ Either adsorbed on the surface of biochar or diffused into the pores, and the negatively charged surface of biochar can promote the positively charged Pb 2+ Electrostatic attraction with biochar, with the increase of pH value, the negative charge on the surface of biochar increases, and its Zeta potential decreases, 2+ The adsorption capacity becomes stronger;
[0032] The negatively charged groups on the biochar surface and the positively charged Pb in the wastewater 2+ Coulomb force is generated to exchange metals in biomass. Metals in biomass cannot be decomposed under high temperature conditions. Higher pyrolysis temperature can promote the enrichment of metals in biochar. K in biochar + 、Na + Mg 2+ The metal content will increase with the increase of pyrolysis temperature. The high activity and fluidity of alkali metals can enhance the ion exchange effect. 2+ With K + and Na + Due to the electrostatic outer sphere complexation, metal exchange occurs, which effectively increases the adsorbent's Pb 2+ Adsorption effect;
[0033] The mineral components in biochar can also enhance the adsorption activity, thereby improving the adsorption performance. Soluble phosphates and carbonates can react with Pb 2+ Co-precipitation forms stable PbCO3. The pH of biochar is generally above 8, which will promote the biochar to Pb 2+ The precipitation effect of Pb 2+ When the pH value of the biochar solution is high, the Pb 2+ It will be converted into hydroxide and precipitated on the surface of biochar. At the same time, the present invention also uses Fe(NO3)3·9H2O to impregnate and pyrolyze biomass to prepare magnetic biochar, so that the adsorbent will produce magnetism to facilitate subsequent separation and treatment.
[0034] (2) The present invention uses lime emulsion as a pH regulator, polyaluminium chloride and polyacrylamide as flocculants and coagulants, respectively, to treat lead-acid battery wastewater. Lime emulsion is added to the wastewater to gradually raise the pH to 7.5-8.5. As the pH in the wastewater increases, the concentration of hydroxide ions in the aqueous solution increases, and the Pb in the water increases. 2+ With OH - Combined to form Pb(OH)2 precipitate, and with OH - As the amount increases, the reaction equilibrium moves toward precipitation. Since the generated Pb(OH)2 precipitate is a fine particle, the sedimentation effect is poor. PAC is an aluminum salt flocculant. After adding it to water, Al 3+ With F - The combination of aluminum salt hydrolysis intermediates and the final Al(OH)3 form various alum flowers in the solution, which have ligand exchange, physical adsorption, and sweeping effects on lead ions. At the same time, it can also promote the formation and growth of Pb(OH)2 precipitation particles, and finally form the generated Pb(OH)2 into water precipitation, which is separated from the treated clean water. Finally, PAM is added to make the suspended matter flocculate through electrical neutralization and bridging adsorption, accelerate the sedimentation of particles in the suspension, and have obvious effects of accelerating solution clarification and promoting filtration. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto. For process parameters not particularly noted, conventional techniques may be used.
[0036] The present invention provides a modified chitosan-based magnetic biochar adsorbent for treating lead-acid battery wastewater. The preparation method of the adsorbent comprises the following steps:
[0037] S1. Mix biomass and Fe(NO3)3·9H2O in a mass ratio of 1:0.5-2, add to anhydrous ethanol, stir evenly at room temperature, and disperse by ultrasonication. Dry at 60-70°C. Place the dried biomass in a container, put it into a tubular furnace and introduce nitrogen. Heat to 500-600°C at a heating rate of 5-10°C / min in a nitrogen atmosphere, sinter at a constant temperature for 2-3h, and cool at room temperature to obtain magnetic biochar.
[0038] S2. Prepare raw materials according to the mass ratio of polypropylene glycol, itaconic anhydride and 4-dimethylaminopyridine of 40:22:0.1-1, stir the polypropylene glycol and heat it to 30-40°C, slowly add itaconic anhydride and 4-dimethylaminopyridine in sequence, then heat it to 50-60°C and stir for 1-2h, cool at room temperature to obtain a modifier.
[0039] S3. According to the weight percentage, weigh 10 to 20 parts of chitosan powder, 100 to 120 parts of 1% acetic acid solution, 6 to 10 parts of magnetic biochar, 12 to 16 parts of modifier, 6 to 8 parts of polyvinyl alcohol, and 40 to 50 parts of 1% sodium tripolyphosphate solution.
[0040] S4. Add chitosan powder to acetic acid solution, stir to dissolve at room temperature, then add magnetic biochar and modifier, stir evenly and heat to 60-70°C in a water bath, then add polyvinyl alcohol and continue stirring until mixed evenly, then slowly add dropwise to sodium tripolyphosphate solution, let stand for aging after the addition is complete, filter, take the solid and dry to obtain a modified chitosan-based magnetic biochar adsorbent.
[0041] Wherein, the biomass in step S1 is at least one of peanut shells, buckwheat shells, coconut skins, wood chips, and bamboo chips.
[0042] The present invention provides a method for treating lead-acid battery wastewater, comprising the following steps:
[0043] (1) Collecting wastewater: Collect the wastewater from lead-acid batteries and store it in a wastewater storage tank. The water quality and quantity of the wastewater are comprehensively adjusted to ensure uniform quality and quantity.
[0044] (2) Primary adsorption treatment: The wastewater in the wastewater storage tank in step (1) is transported to the primary adsorption tank, the pH value is adjusted to 5-6, and the adsorbent is added at a dosage of 0.5-1.5 g / L for adsorption treatment for 6-10 hours, and filtered to obtain the filtrate of the primary adsorption treatment.
[0045] (3) Reaction treatment: Add the filtrate from the primary adsorption treatment in step (2) into the reaction tank at a rate of 2 to 3 kg / m 3 Add lime emulsion at a dosage of 0.1-0.45 kg / m 3 Add Al2O3 with a content of 20% to 30% to polyaluminium chloride for reaction. After the reaction is completed, press 0.005 to 0.01 kg / m 3 Polyacrylamide with a molecular weight of 10 million to 14 million is added for flocculation to obtain a mud-water mixture.
[0046] (4) Sedimentation treatment: The mud-water mixture in step (3) is transported to a sedimentation tank, and the surface load of the sedimentation tank is controlled to be 0.1 to 1.0 m 3 / (m2·h), the physicochemical sludge produced by the sedimentation reaction, the upper clear liquid and the lower sludge are collected.
[0047] (5) Dehydration treatment: The lower layer of sludge in step (4) is transported to a sludge thickening tank for reduction adjustment, and then pumped into a high-pressure diaphragm plate and frame filter press for further dehydration and reduction to obtain filter press filtrate and dehydrated sludge.
[0048] (6) Secondary adsorption treatment: The supernatant in step (3) and the filter press filtrate in step (5) are mixed and transported to a secondary adsorption tank, the pH value is adjusted to 6 to 9, and an adsorbent is added at a dosage of 0.5 to 1.5 g / L for adsorption treatment for 6 to 10 hours. The mixture is filtered to obtain a filtrate treated with secondary adsorption.
[0049] (7) Testing and collection: The filtrate from the secondary adsorption treatment in step (6) is tested. If the filtrate meets the test standards, it is collected and sent to a clean water tank. If the filtrate does not meet the test standards, it is returned to the primary adsorption tank or the secondary adsorption tank for further treatment according to the standards until it meets the test standards.
[0050] Example 1
[0051] The preparation method of the modified chitosan-based magnetic biochar adsorbent of this embodiment comprises the following steps:
[0052] S1. Mix peanut shells and Fe(NO3)3·9H2O in a mass ratio of 1:0.5 and add them to anhydrous ethanol. Stir them evenly at room temperature and disperse them by ultrasonic. Dry them at 60°C. Put the dried biomass in a container, put it in a tubular furnace and introduce nitrogen. Heat it to 500°C at a heating rate of 5°C / min in a nitrogen atmosphere, sinter it at a constant temperature for 2h, and cool it at room temperature to obtain magnetic biochar.
[0053] S2. Prepare raw materials according to the mass ratio of polypropylene glycol, itaconic anhydride and 4-dimethylaminopyridine of 40:22:0.1, stir the polypropylene glycol and heat it to 30°C, slowly add itaconic anhydride and 4-dimethylaminopyridine in sequence, then heat it to 50°C and stir for 1h, cool at room temperature to obtain a modifier.
[0054] S3. According to the weight percentage, weigh 10 parts of chitosan powder, 100 parts of 1% acetic acid solution, 6 parts of magnetic biochar, 12 parts of modifier, 6 parts of polyvinyl alcohol, and 40 parts of 1% sodium tripolyphosphate solution.
[0055] S4. Add chitosan powder to acetic acid solution, stir to dissolve at room temperature, then add magnetic biochar and modifier, stir evenly and heat to 60°C in a water bath, then add polyvinyl alcohol and continue stirring until mixed evenly, then slowly add dropwise to sodium tripolyphosphate solution, let stand for aging after the addition is complete, filter, take the solid and dry to obtain a modified chitosan-based magnetic biochar adsorbent.
[0056] Example 2
[0057] The preparation method of the modified chitosan-based magnetic biochar adsorbent of this embodiment comprises the following steps:
[0058] S1. Buckwheat husk and Fe(NO3)3·9H2O were mixed in a mass ratio of 1:1 and added to anhydrous ethanol. The mixture was stirred evenly at room temperature and then dispersed by ultrasonic. The mixture was dried at 65°C. The dried biomass was placed in a container, put into a tubular furnace and introduced with nitrogen. The temperature was increased to 540°C at a heating rate of 8°C / min in a nitrogen atmosphere. The mixture was sintered at a constant temperature for 2.5 h and cooled at room temperature to obtain magnetic biochar.
[0059] S2. Prepare raw materials according to the mass ratio of polypropylene glycol, itaconic anhydride and 4-dimethylaminopyridine of 40:22:0.5, stir the polypropylene glycol and heat it to 35°C, slowly add itaconic anhydride and 4-dimethylaminopyridine in sequence, then heat it to 55°C and stir for 1-2h, cool at room temperature to obtain a modifier.
[0060] S3. According to the weight percentage, weigh 15 parts of chitosan powder, 110 parts of 1% acetic acid solution, 8 parts of magnetic biochar, 14 parts of modifier, 7 parts of polyvinyl alcohol, and 45 parts of 1% sodium tripolyphosphate solution.
[0061] S4. Add chitosan powder to acetic acid solution, stir to dissolve at room temperature, then add magnetic biochar and modifier, stir evenly and heat to 65°C in a water bath, then add polyvinyl alcohol and continue stirring until mixed evenly, then slowly add dropwise to sodium tripolyphosphate solution, let stand for aging after the addition is complete, filter, take the solid and dry it to obtain a modified chitosan-based magnetic biochar adsorbent.
[0062] Example 3
[0063] The preparation method of the modified chitosan-based magnetic biochar adsorbent of this embodiment comprises the following steps:
[0064] S1. Mix coconut peel and Fe(NO3)3·9H2O in a mass ratio of 1:2 and add them to anhydrous ethanol. Stir them evenly at room temperature and disperse them by ultrasonic. Dry them at 70°C. Put the dried biomass in a container, put it in a tubular furnace and introduce nitrogen. Heat it to 600°C at a heating rate of 10°C / min in a nitrogen atmosphere, sinter them at a constant temperature for 3h, and cool them at room temperature to obtain magnetic biochar.
[0065] S2. Prepare raw materials according to the mass ratio of polypropylene glycol, itaconic anhydride and 4-dimethylaminopyridine of 40:22:1, stir the polypropylene glycol and heat it to 40°C, slowly add itaconic anhydride and 4-dimethylaminopyridine in sequence, then heat it to 60°C and stir for 2h, cool at room temperature to obtain a modifier.
[0066] S3. According to the weight percentage, weigh 20 parts of chitosan powder, 120 parts of 1% acetic acid solution, 10 parts of magnetic biochar, 16 parts of modifier, 8 parts of polyvinyl alcohol, and 50 parts of 1% sodium tripolyphosphate solution.
[0067] S4. Add chitosan powder to acetic acid solution, stir to dissolve at room temperature, then add magnetic biochar and modifier, stir evenly and heat to 70°C in a water bath, then add polyvinyl alcohol and continue stirring until mixed evenly, then slowly add dropwise to sodium tripolyphosphate solution, let stand for aging after the addition is complete, filter, take the solid and dry it to obtain a modified chitosan-based magnetic biochar adsorbent.
[0068] Example 4
[0069] The adsorbent used in the treatment of lead-acid battery wastewater in this embodiment is the modified chitosan-based magnetic biochar adsorbent prepared in Example 1. The lead-acid battery wastewater treatment method in this embodiment includes the following steps:
[0070] (1) Collecting wastewater: Collect the wastewater from lead-acid batteries and store it in a wastewater storage tank. The water quality and quantity of the wastewater are comprehensively adjusted to ensure uniform quality and quantity.
[0071] (2) Primary adsorption treatment: The wastewater in the wastewater storage tank in step (1) is transported to the primary adsorption tank, the pH value is adjusted to 5, and the adsorbent is added at a dosage of 0.5 g / L for adsorption treatment for 6 hours, and filtered to obtain the filtrate of the primary adsorption treatment.
[0072] (3) Reaction treatment: The filtrate from the primary adsorption treatment in step (2) was added to the reaction tank at a rate of 2 kg / m 3 Add lime emulsion at a dosage of 0.1 kg / m 3 Add 20% Al2O3 to polyaluminium chloride for reaction. After the reaction is completed, press 0.005kg / m 3 Polyacrylamide with a molecular weight of 10 million is added for flocculation to obtain a mud-water mixture.
[0073] (4) Sedimentation treatment: The mud-water mixture in step (3) is transported to a sedimentation tank, and the surface load of the sedimentation tank is controlled to be 0.1 m 3 / (m2·h), the physicochemical sludge produced by the sedimentation reaction, the upper clear liquid and the lower sludge are collected.
[0074] (5) Dehydration treatment: The lower layer of sludge in step (4) is transported to a sludge thickening tank for reduction adjustment, and then pumped into a high-pressure diaphragm plate and frame filter press for further dehydration and reduction to obtain filter press filtrate and dehydrated sludge.
[0075] (6) Secondary adsorption treatment: The supernatant in step (3) and the filter press filtrate in step (5) are mixed and transported to a secondary adsorption tank, the pH value is adjusted to 6, and an adsorbent is added at a dosage of 0.5 g / L for adsorption treatment for 6 hours. The mixture is filtered to obtain a filtrate treated with secondary adsorption.
[0076] (7) Testing and collection: The filtrate from the secondary adsorption treatment in step (6) is tested. If the filtrate meets the test standards, it is collected and sent to a clean water tank. If the filtrate does not meet the test standards, it is returned to the primary adsorption tank or the secondary adsorption tank for further treatment according to the standards until it meets the test standards.
[0077] Example 5
[0078] The adsorbent used in the treatment of lead-acid battery wastewater in this embodiment is the modified chitosan-based magnetic biochar adsorbent prepared in Example 2. The lead-acid battery wastewater treatment method in this embodiment includes the following steps:
[0079] (1) Collecting wastewater: Collect the wastewater from lead-acid batteries and store it in a wastewater storage tank. The water quality and quantity of the wastewater are comprehensively adjusted to ensure uniform quality and quantity.
[0080] (2) Primary adsorption treatment: The wastewater in the wastewater storage tank in step (1) is transported to the primary adsorption tank, the pH value is adjusted to 5.5, and the adsorbent is added at a dosage of 1 g / L for adsorption treatment for 8 hours, and filtered to obtain the filtrate of the primary adsorption treatment.
[0081] (3) Reaction treatment: The filtrate from the primary adsorption treatment in step (2) was added to the reaction tank at a rate of 2.5 kg / m 3 Add lime emulsion at a dosage of 0.25kg / m 3 Add 25% Al2O3 to polyaluminium chloride for reaction. After the reaction is completed, press 0.007kg / m 3 Polyacrylamide with a molecular weight of 12 million is added for flocculation to obtain a mud-water mixture.
[0082] (4) Sedimentation treatment: The mud-water mixture in step (3) is transported to a sedimentation tank, and the surface load of the sedimentation tank is controlled to be 0.5 m 3 / (m2·h), the physicochemical sludge produced by the sedimentation reaction, the upper clear liquid and the lower sludge are collected.
[0083] (5) Dehydration treatment: The lower layer of sludge in step (4) is transported to a sludge thickening tank for reduction adjustment, and then pumped into a high-pressure diaphragm plate and frame filter press for further dehydration and reduction to obtain filter press filtrate and dehydrated sludge.
[0084] (6) Secondary adsorption treatment: The supernatant in step (3) and the filter press filtrate in step (5) are mixed and transported to a secondary adsorption tank, the pH value is adjusted to 7, and an adsorbent is added at a dosage of 1 g / L for adsorption treatment for 8 hours. The mixture is filtered to obtain a filtrate treated with secondary adsorption.
[0085] (7) Testing and collection: The filtrate from the secondary adsorption treatment in step (6) is tested. If the filtrate meets the test standards, it is collected and sent to a clean water tank. If the filtrate does not meet the test standards, it is returned to the primary adsorption tank or the secondary adsorption tank for further treatment according to the standards until it meets the test standards.
[0086] Example 6
[0087] The adsorbent used in the treatment of lead-acid battery wastewater in this embodiment is the modified chitosan-based magnetic biochar adsorbent prepared in Example 3. The lead-acid battery wastewater treatment method in this embodiment includes the following steps:
[0088] (1) Collecting wastewater: Collect the wastewater from lead-acid batteries and store it in a wastewater storage tank. The water quality and quantity of the wastewater are comprehensively adjusted to ensure uniform quality and quantity.
[0089] (2) Primary adsorption treatment: The wastewater in the wastewater storage tank in step (1) is transported to the primary adsorption tank, the pH value is adjusted to 6, and the adsorbent is added at a dosage of 1.5 g / L for adsorption treatment for 10 hours, and filtered to obtain the filtrate of the primary adsorption treatment.
[0090] (3) Reaction treatment: Add the filtrate from the primary adsorption treatment in step (2) into the reaction tank at a rate of 2 to 3 kg / m 3 Add lime emulsion at a dosage of 0.45kg / m 3 Add 30% Al2O3 to polyaluminium chloride for reaction. After the reaction is completed, press 0.01kg / m 3 Polyacrylamide with a molecular weight of 14 million is added at a dosage for flocculation to obtain a mud-water mixture.
[0091] (4) Sedimentation treatment: The mud-water mixture in step (3) is transported to a sedimentation tank, and the surface load of the sedimentation tank is controlled to be 1.0 m 3 / (m2·h), the physicochemical sludge produced by the sedimentation reaction, the upper clear liquid and the lower sludge are collected.
[0092] (5) Dehydration treatment: The lower layer of sludge in step (4) is transported to a sludge thickening tank for reduction adjustment, and then pumped into a high-pressure diaphragm plate and frame filter press for further dehydration and reduction to obtain filter press filtrate and dehydrated sludge.
[0093] (6) Secondary adsorption treatment: The supernatant in step (3) and the filter press filtrate in step (5) are mixed and transported to a secondary adsorption tank, the pH value is adjusted to 8, and an adsorbent is added at a dosage of 1.5 g / L for adsorption treatment for 10 hours. The mixture is filtered to obtain a filtrate treated with secondary adsorption.
[0094] (7) Testing and collection: The filtrate from the secondary adsorption treatment in step (6) is tested. If the filtrate meets the test standards, it is collected and sent to a clean water tank. If the filtrate does not meet the test standards, it is returned to the primary adsorption tank or the secondary adsorption tank for further treatment according to the standards until it meets the test standards.
[0095] Comparative Example 1
[0096] The lead-acid battery wastewater treatment method of this comparative example is substantially the same as the treatment method of Example 4, the difference being that the adsorbents used in the primary adsorption treatment and the secondary adsorption treatment of this comparative example are both activated carbon.
[0097] Comparative Example 2
[0098] The lead-acid battery wastewater treatment method of this comparative example is a coagulation sedimentation method. In this method, the oil substances are first separated by a grease trap and then enter the neutralization tank. The pH of the wastewater is adjusted to about 6 in the primary pH adjustment tank, and a flocculant, polyaluminium chloride, and a coagulant aid, polyacrylamide, are added to remove some of the pollutants, Pb 2+ Then, in order to fully precipitate Pb 2+ , the pH is adjusted to about 10.5 in the secondary pH adjustment tank, and then solid-liquid separation is carried out through the inclined plate sedimentation tank. After separation, part of the wastewater is used as recycled water, and the rest of the wastewater enters the acid adjustment tank. The sludge is compacted by the filter press and then transported to the entrusted treatment agency. The wastewater after acid adjustment enters the mechanical filter through the intermediate water pump to remove suspended impurities.
[0099] Experimental example
[0100] The water quality of the lead-acid battery wastewater treated in Examples 4 to 6 and Comparative Examples 1 to 2 is shown in Table 1:
[0101] Table 1: Lead-acid battery wastewater quality table
[0102]
[0103] The effluent water quality complies with the "Battery Industry Pollutant Emission Standard" (GB30484-2013), and the pH value, total lead, suspended solids content and chemical oxygen demand of the effluent water quality of Examples 4 to 6 and Comparative Examples 1 to 2 are tested respectively. The specific test results are shown in Table 2:
[0104] Table 2: Statistics of effluent water quality test results
[0105]
[0106] As shown in Table 2, by comparing Example 4 with Comparative Example 1, the adsorbent of the present invention has better adsorption performance than activated carbon. This is because the present invention uses polypropylene glycol and itaconic anhydride to structurally transform chitosan, introduce more active sites on chitosan to improve its adsorption capacity, and increase the porosity of the adsorbent while protecting the hydroxyl and amino groups on the surface of chitosan, making the surface of the adsorbent rough and not smooth, thereby increasing the surface area of the adsorbent, which is beneficial to the adsorption of Pb 2+ Contact with the adsorbent makes more active sites on the adsorbent surface available, thereby improving the adsorption capacity. 2+ The lone pair of electrons on the O atom of the ether bond is used to form a bond, which reduces the electron density of the adjacent C atom and forms a CO-Pb bond, thereby further improving the adsorbent's affinity for Pb. 2+ adsorption effect.
[0107] By comparing Example 4 with Comparative Example 2, the total lead content of the effluent treated by the lead-acid battery wastewater treatment method of the present invention is lower than 0.2 mg / L. This is because the present invention uses chitosan as a carrier, modifies it and loads magnetic biochar as an adsorbent. There are a large number of hydroxyl and amino groups in the chitosan molecule as active sites, which can bind to Pb through chelation, hydrogen bonding or electrostatic attraction. 2+ The biochar forms a complex by π-π interaction and hydrogen bonding. 2+ Adsorbed onto oxygen-containing functional groups such as C=O, CO and OH of the material, the negatively charged groups on the surface of biochar and the positively charged Pb 2+ Coulomb force is generated and exchanged, K in biochar + 、Na + Mg 2+ The metal content will increase with the increase of pyrolysis temperature. The high activity and fluidity of alkali metals can enhance the ion exchange effect. 2+ With K + and Na + Due to the electrostatic outer sphere complexation, metal exchange occurs, which effectively increases the adsorbent's Pb 2+ adsorption effect.
[0108] Therefore, the lead-acid battery wastewater treatment method of the present invention is simple to operate, can effectively treat lead ions and suspended matter in wastewater, and has broad application prospects.
[0109] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for treating lead-acid battery wastewater, characterized in that: The following steps are involved: (1) Collecting wastewater: Collecting lead-acid battery wastewater and storing it in a wastewater storage tank, and comprehensively adjusting the water quality and water volume of the lead-acid battery wastewater to ensure uniform quality and volume; (2) Primary adsorption treatment: The wastewater in the wastewater storage tank in step (1) is transported to the primary adsorption tank, the pH value is adjusted to 5-6, an adsorbent is added at a dosage of 0.5-1.5 g / L for adsorption treatment for 6-10 hours, and filtered to obtain a filtrate of the primary adsorption treatment; (3) Reaction treatment: adding the filtrate from the primary adsorption treatment in step (2) into a reaction tank, adding lime emulsion to adjust the pH value to 7.5-8.5, then adding polyaluminium chloride to react, and after the reaction is completed, adding polyacrylamide to flocculate to obtain a mud-water mixture; (4) Sedimentation treatment: The mud-water mixture in step (3) is transported to a sedimentation tank to produce physicochemical sludge by sedimentation reaction, and the upper clear liquid and lower sludge are collected; (5) Dehydration treatment: The lower layer of sludge in step (4) is transported to a sludge thickening tank for reduction adjustment, and then pumped into a high-pressure diaphragm plate and frame filter press for further dehydration and reduction to obtain a filter press filtrate and dehydrated sludge; (6) Secondary adsorption treatment: the supernatant in step (3) and the filter press filtrate in step (5) are mixed and transported to a secondary adsorption tank, the pH value is adjusted to 6 to 9, an adsorbent is added at a dosage of 0.5 to 1.5 g / L for 6 to 10 hours, and filtered to obtain a filtrate treated with secondary adsorption; (7) Testing and collection: Testing the filtrate from the secondary adsorption treatment in step (6). If the filtrate meets the standard, it is collected and put into the clean water tank. If it does not meet the standard, it is returned to the primary adsorption tank or the secondary adsorption tank according to the standard for further treatment until it meets the standard. Wherein, the adsorbents in step (2) and step (6) are both modified chitosan-based magnetic biochar adsorbents.
2. The lead-acid battery wastewater treatment method according to claim 1, characterized in that: The dosage of lime emulsion in step (3) is 2-3 kg / m 3 .
3. The lead-acid battery wastewater treatment method according to claim 1, characterized in that: In the step (3), the Al2O3 content in the polyaluminium chloride is 20% to 30%, and the dosage of the polyaluminium chloride is 0.1 to 0.45 kg / m 3 .
4. The lead-acid battery wastewater treatment method according to claim 1, characterized in that: In the step (3), the molecular weight of polyacrylamide is 10 million to 14 million, and the dosage of polyacrylamide is 0.005 to 0.01 kg / m 3 .
5. The lead-acid battery wastewater treatment method according to claim 1, characterized in that: The sedimentation tank in step (4) is a vertical flow type, and the surface load of the sedimentation tank is 0.1 to 1.0 m 3 / (m2·h).
6. The lead-acid battery wastewater treatment method according to claim 1, characterized in that: The preparation method of the modified chitosan-based magnetic biochar adsorbent comprises the following steps: S1. Mix the biomass with Fe(NO3)3·9H2O and add them to anhydrous ethanol, stir them evenly at room temperature and disperse them by ultrasonication, dry them at 60-70°C, put the dried biomass in a container, put it in a tubular furnace and introduce nitrogen, heat it to 500-600°C in a nitrogen atmosphere, sinter it at a constant temperature, and cool it at room temperature to obtain magnetic biochar; S2, stirring the polypropylene glycol and heating it to 30-40°C, slowly adding itaconic anhydride and 4-dimethylaminopyridine in sequence, then heating it to 50-60°C and stirring for 1-2h, and cooling it at room temperature to obtain a modifier; S3, weigh 10-20 parts of chitosan powder, 100-120 parts of 1% acetic acid solution, 6-10 parts of magnetic biochar, 12-16 parts of modifier, 6-8 parts of polyvinyl alcohol, and 40-50 parts of 1% sodium tripolyphosphate solution respectively by weight; S4. Add chitosan powder to acetic acid solution, stir to dissolve at room temperature, then add magnetic biochar and modifier, stir evenly and heat to 60-70°C in a water bath, then add polyvinyl alcohol and continue stirring until mixed evenly, then slowly add dropwise to sodium tripolyphosphate solution, let stand for aging after the addition is complete, filter, take the solid and dry to obtain a modified chitosan-based magnetic biochar adsorbent.
7. The lead-acid battery wastewater treatment method according to claim 6, characterized in that: The biomass in step S1 is at least one of peanut shells, buckwheat shells, coconut skins, wood chips, and bamboo chips.
8. The lead-acid battery wastewater treatment method according to claim 6, characterized in that: The mass ratio of the biomass to Fe(NO3)3·9H2O in step S1 is 1:0.5-2.
9. The lead-acid battery wastewater treatment method according to claim 6, characterized in that: The heating rate in step S1 is 5-10° C. / min, and the sintering time is 2-3 hours.
10. The lead-acid battery wastewater treatment method according to claim 6, characterized in that: The mass ratio of polypropylene glycol, itaconic anhydride and 4-dimethylaminopyrrolidone in step S2 is 40:22:0.1-1.
Citation Information
Patent Citations
Method for processing wastewater containing lead by combining flocculent precipitation with adsorption filtration
CN103708649A
Preparation method and application of DPTA-chitosan modified magnetic adsorbent
CN105921134A
Electroplating wastewater treatment device
CN206635175U
Industrial wastewater decolorization treatment system
CN211339076U
Method for producing metal adsorbent containing acetylated chitosan fine particles and method for producing acetylated chitosan fine particles
JP2014057963A
Cited By
Efficient combined flocculant for micro-fine-particle high-talc copper-cobalt ore and application method of efficient combined flocculant
CN120789727A
Efficient combined flocculant for micro-fine high-talc-copper-cobalt ore and application method thereof
CN120789727B